2013
DOI: 10.1371/journal.pone.0053830
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Genetic Architecture of Early Stage Age-Related Macular Degeneration: A Genome-Wide Association Study Meta-Analysis

Abstract: Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 66 publications
8
106
0
1
Order By: Relevance
“…Previous genome-wide association studies have identified numerous risk-associated variants within 19 susceptibility loci for AMD [6][7][8][9][10] . However, genome-wide association studies focus on common variants (minor allele frequency (MAF) 45%), which are usually located in the intronic regions of the chromosome and do not encode specific functional proteins 11,12 .…”
mentioning
confidence: 99%
“…Previous genome-wide association studies have identified numerous risk-associated variants within 19 susceptibility loci for AMD [6][7][8][9][10] . However, genome-wide association studies focus on common variants (minor allele frequency (MAF) 45%), which are usually located in the intronic regions of the chromosome and do not encode specific functional proteins 11,12 .…”
mentioning
confidence: 99%
“…Rs2075650 within APOE/TOMM40 has been studied for its associations with several age-related disorders and diseases in GWAS, such as cognitive decline 27,28 and Alzheimer's disease (AD), [29][30][31] as well as AMD. 12,13 Apolipoprotein E (ApoE), encoded by the APOE gene, was recognized for its crucial role in lipoprotein transport. An endogenous way of retinal lipid removal may rely on the components of reverse cholesterol transport including ApoE.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, this variant has been identified showing association with early AMD in a GWAS meta-analysis of European population (P ¼ 1.1 Â 10 À6 ), and the signal remained in secondary meta-analysis combining two Singapore-based Asian cohorts (P ¼ 3.2 Â 10 À6 ). 13 However, Guo et al 14 failed to replicate the association between this variant and neovascular AMD, the CNV subtype of advanced AMD in a northern Chinese cohort (P ¼ 0.912), which could be due to the phenotypic discrepancy between AMD subtypes and overall advanced AMD, as well as the genetic discrepancy between different ethnic groups. As no genetic association study of rs2075650 has been performed for overall advanced AMD in Chinese population before, to shed a light on the source of these contradicting results, it is necessary to study the potential impact of rs2075650 on overall advance AMD risk in Chinese population.…”
Section: à8mentioning
confidence: 99%
“…The second sample (T0) was performed 20 minutes after the collection of T0', regardless of the time taken by participants to eat the meal. According to randomization, participants then consumed 100 mL of a drink containing either 8.2 g of Prolacta ® (PRO8), 5 g of Prolacta ® (PRO5) or 0 g of Prolacta ® [11] over a maximum of 2 minutes ( Table 2). The consumption of the standardized lunch in addition to the control drink was considered the control meal, providing 27 g of proteins and 2.2 g of leucine.…”
Section: Experimental Protocolmentioning
confidence: 99%